Clinical Toxicology of OTC Cough and Cold Pediatric Medications: A Narrative Review - Diantini A; Alfaqeeh M; Permatasari LI; Nurfitriani M; Durotulailah L; Wulandari W; Sitorus TDR; Wilar G; Levita J (Dove Medical Press, 2024)
Ajeng Diantini,1,2,* Mohammed Alfaqeeh,3,* Lanny Indah Permatasari,3,* Mirna Nurfitriani,3,* Lela Durotulailah,3,* Wening Wulandari,3,* Truly Deti Rose Sitorus,4 Gofarana Wilar,1,2 Jutti Levita1,2,* 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran. University, Sumedang, West Java, 45363, Indonesia; 2Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Padjadjaran University, Sumedang, West Java, 45363, Indonesia; 3Master Program in Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 45363, Indonesia; 4Department of Pharmacology and Therapy, Faculty of Medicine, Padjadjaran University, Sumedang, West Java, 45363, Indonesia*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia, Tel +6222-84288888 Ext 3510, Email jutti.levita@unpad.ac.idAbstract: Cough and cold symptoms (CCS) are common pediatric conditions often treated with over-the-counter (OTC) medications. However, the available knowledge regarding the safety and toxicity of these medications in children is inadequate. Therefore, understanding their clinical toxicology is crucial for safeguarding children's well-being. This narrative review highlights the importance of clinical toxicology in evaluating the safety and toxicity profile of OTC medications for treating CCS in pediatric patients. The pharmacology, clinical features, and adverse effects of various drug classes commonly found in cough and cold medications are briefly discussed. Pharmacokinetic and pharmacodynamic parameters are also examined to understand the interactions between these drugs and the body. OTC cough and cold medications often contain active ingredients such as antihistamines, decongestants, antitussives, expectorants, and analgesics-antipyretics. The combination of multiple ingredients in these products significantly increases the risk of adverse effects and unintentional overdoses. Several case studies have reported significant toxicity and even fatalities associated with the use of these medications in children. This review underscores the critical importance of clinical toxicology in evaluating the safety and toxicity profile of OTC medications employed for treating CCS in pediatric patients. The findings highlight the significance of informed clinical practice and public health policies to ensure the well-being of children using OTC cough and cold medications.Keywords: bromhexine, chlorpheniramine maleate, dextromethorphan, glyceryl guaiacolate, paracetamol, pseudoephedrine